Antibacterial test of Peperomia pellucida (L.) Kunth extract against Porphyromonas Gingivalis as a potential herb for periodontitis: a laboratory experiment - Nasution, Dewi Lidya Ichwana; Tjahajawati, Sri; Indriyanti, Ratna; Amaliya, Amaliya; Fadilah, Rina Putri Noer; Mutiara, Rahman (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Periodontitis is a multifactorial inflammatory disease which is generally caused by plaque accumulation. Many studies have shown that Porphyromonas gingivalis (Pg) is the main etiological agent that contributes to chronic periodontitis. Scaling and root planing (SRP) is the gold standard for periodontitis treatment. The use of antibiotics as additional agents accompanying the SRP procedure has limitations that can cause resistance to subgingival periodontal pathogens. Peperomia pellucida (L.) Kunth i.e betel leaf is a natural ingredient that contains anti-inflammatory, antibacterial and antioxidant properties. This study aimed to analyze the inhibition of Peperomia pellucida (L.) Kunth  extract against Pg bacteria. Methods: The type of study used was an experimental laboratory with a Post-Test Control Group Design research design which was divided into 6 treatment groups using the disk diffusion method with concentrations of Peperomia pellucida (L.) Kunth extract 25, 50, 75 and 100%, sterile aquades as a negative control and Chlorhexidine as a positive control. Data analyses of One Way Anova and Post Hoc Tukey were used Results: Peperomia pellucida (L.) Kunth extract concentrations of 25, 50, 75, and 100% had an  effect on reducing the growth of Porphyromonas gingivalis (p≤0,05), the average inhibition response was 14.40 mm at 25% concentration, 16.58 mm at 50% concentration and 19.30 mm at 75%, 21.88 mm at 100% concentration.Conclusion: Peperomia pellucida (L.) Kunth extract has an antibacterial effect against Porphyromonas gingivalis which has the potential to be used as a periodontitis herb.Keywords: Betel leaf extract Peperomia pellucida (L.) Kunth, periodontitis, Porphyromonas gingivalis.